Soil health indicator variability and management sensitivity across soils, bioregions, and agricultural systems - Katherine A. Dynarski; Ekundayo Adeleke; R. Louis Baumhardt; Joseph Burke; Tiffany Carter; Paul DeLaune; Huijie Gan; Julie Grossman; Josh Heitman; Divya Kandanool; Katie Lewis; Katherine Naasko; et al. (Agriculture, Ecosystems & Environment, 2026)

Nitrogen fixation and productivity of winter annual legume cover crops in Upper Midwest organic cropping systems - Sharon Perrone; Julie Grossman; Alex Liebman; Thanwalee Sooksa-nguan; Jessica Gutknecht (Nutrient Cycling in Agroecosystems, 2020)
Legume cover crops can play a valuable role in maintaining and increasing soil quality and nitrogen availability, but are infrequently grown in the Upper Midwest due to short growing seasons with minimal management windows; cold, wet springs; and harsh winters. This study was performed to assess the viability of winter annual legume species in northern climates as a potential source of nitrogen (N) fertility to a 75-day sweet corn ( Zea mays convar. s accharata var. rugosa ) cash crop in Lamberton and Grand Rapids, MN in 2016 and 2017. Treatments included medium red clover ( Trifolium pratense ), two cold-hardy ecotypes of hairy vetch ( Vicia villosa Roth), a cereal rye-hairy vetch biculture ( Secale cereale L., Vicia villosa Roth), cereal rye as a non-legume control, and a fallow weed-free control. Legumes were split into rhizobia inoculated and non-inoculated treatments. Inoculation had no effect on nodulation, biomass production, or N fixation likely due to competition with endogenous rhizobia strains. The rye monoculture and biculture produced the most biomass at all site-years averaging 7.7 and 7.0 Mg ha −1 respectively while the two vetch ecotypes averaged 4.5 and 3.9 Mg ha −1 . Both vetch ecotypes contributed among the most nitrogen in all site-years, contributing up to 211 kg N ha −1 from aboveground biomass. Data from natural abundance isotopic approaches indicate that 75% of vetch tissue N in Grand Rapids and 59% of vetch tissue N in Lamberton was derived from atmospheric N fixation, with equal or higher percent fixation of vetch in biculture at all site-years. More studies should be performed to better understand controls on N fixation of legume cover crops in cold climates.